RUMAH GADANG : RUANG DAN BUDAYA MAKAN DALAM SIKLUS HIDUP MASYARAKAT MINANGKABAU - Vania Dwi Amanda Surya; Gregorius Prasetyo Adhitama (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2021)
Padang restaurants with specialty food rendang represent the Minangkabau's eating culture. The effect of modernization and media social in the eating culture has indistinct the origin of Minangkabau's eating culture and leads to the uniformity of design, mostly its space and physical elements in the traditional building. Whereas in the roots, eating activities according to the Minangkabau custom still carried out, such as Makan Bajamba. It is essential to study the origin of Minangkabau space and eating culture before learning design development. The main problem is how the relationship between space and eating culture in the life cycle of Minangkabau society carried out at Rumah Gadang. By using a mix-method, a qualitative approach is a case study at Rumah Gadang Istana Rajo Alam Tuanku Disambah and quantitative approaches using space syntax analysis on the dimensions of connectivity and integrity. Data were from literature studies, interviews, and direct observations on how Rumah Gadang facilitated eating activities. The result shows that Rumah Gadang effectively assisted the eating culture in the life cycle of its people. The space configuration in the process of eating activities is following the roles of women and men based on a matrilineal kinship system. The seat position rules for Minangkabau men from the matrilineal kinship system divided Ruang Lepas into smaller areas, marked by walls, columns, and seprah clothes. All space of eating activities is a social space where interactions took place as a reflection of Minangkabau customs. The space syntax analysis clarifies the relationship between space and eating activities based on the matrilineal kinship system and the social interactions that occur with the space used. For future research, the space syntax analysis is useful as a perspective to learn the relationship between space and culture.